Investigation of datum constraints effect in terrestrial laser scanner self-calibration - Abbas, Mohd. Azwan (Penerbit UTM Press, 2015)
The ability to provide rapid and dense three-dimensional (3D) data have made many 3D applications easier. However, similar to other optical and electronic instruments, data from TLS can also be impaired with errors. Self-calibration is a method available to investigate those errors in TLS observations which has been adopted from photogrammetry technique. Though, the network configuration applied by both TLS and photogrammetry techniques are quite different. Thus, further investigation is required to verify whether the photogrammetry principal regarding datum constraints selection is applicable to TLS self-calibration. To ensure that the assessment is thoroughly done, the datum constraints analyses were carried out using three variant network configurations: 1) minimum number of scan stations, 2) minimum number of surfaces for targets distribution, and 3) minimum number of point targets. Via graphical and statistical, the analyses of datum constraints selection have indicated that the parameter correlations obtained are significantly similar.